Phenotype and Genotype Study of Chinese POMT2-Related α-Dystroglycanopathy - Chen, Xiao-Yu; Song, Dan-Yu; Jiang, Li; Tan, Dan-Dan; Liu, Yi-Dan; Liu, Jie-Yu; Chang, Xing-Zhi; Xing, Guo-Gang; Toda, Tatsushi; Xiong, Hui (Frontiers in Genetics, 2021)
Objective Alpha-dystroglycanopathy (α-DGP) is a subtype of muscular dystrophy caused by defects in the posttranslational glycosylation of α-dystroglycan (α-DG). Our study aimed to summarize the clinical and genetic features of POMT2-related α-DGP in a cohort of patients in China. Methods Pedigrees, clinical data and laboratory tests of patients diagnosed with POMT2-related α-DGP were analyzed retrospectively. The pathogenicity of variants in POMT2 were predicted by bioinformatics software. The variants with uncertain significance were verified by further analysis. Results The eleven patients, comprising eight males and three females, were from nine nonconsanguineous families. They exhibited different degrees of muscle weakness, ambulation and intellectual impairment. Among them, three had a muscle-eye-brain disease (MEB)-like phenotype, five presented congenital muscular dystrophy with intellectual disability (CMD-ID), and three presented limb-girdle muscular dystrophy (LGMD). Overall, nine novel variants of POMT2, including two nonsense, one frameshift and six missense variants, were identified. The pathogenicity of two missense variants, c.1891G>C and c.874G>C, was uncertain based on bioinformatics software prediction. In vitro minigene analysis showed that c.1891G>C affects the splicing of POMT2. Immunofluorescence staining with the IIH6C4 antibody of muscle biopsy from the patient carrying the c.874G>C variant showed an apparent lack of expression. Conclusion This study summarizes the clinical and genetic characteristics of a cohort of POMT2-related α-DGP patients in China for the first time, expanding the mutational spectrum of the disease. Further study of the pathogenicity of some missense variants based on enzyme activity detection is needed.